Understanding extreme violent behavior in ultra firms: exploring identity fusion from a dialogical perspective - Silva, J. R.; Da Silva, R.; Fernández-Navarro, P.; Rosa, C.; Gonçalves, M. M. (Journal of Constructivist Psychology, 2020)
This paper explores a dialogical operationalization of identity fusion in the context of football firms. An in-depth life story interview with a longstanding member of a football firm involved in several violent episodes was qualitatively analyzed. The variety of positions of the self (I-positions) as well as the dialogical relations established by such positions were examined under themes associated with identity fusion, in an attempt to understand pro-group radical violent behavior. Results suggest that a core coalition of internal I-positions and external We-positions favoring extreme ultra violence appeared to dominate the participant’s self-system. This coalition seemed to have soft boundaries among the positions compounding it and, at the same time, rigid boundaries with other positions of the self-system, operating as an I-prison, preventing alternative counter-violence voices to be heard and promoter or meta-positions to emerge. Considering that functionally equivalent forms of identity fusion have been identified in radical football violence and terrorism, this knowledge can contribute to tackle the pathways for engaging in extreme violence in favor of a group/organization. Moreover, it can be used to develop more effective programs to promote individuals’ de-fusion from different groups, whenever group adherence proves dysfunctional and risky for themselves and/or others.